Early marriage, adolescent motherhood, and reproductive rights for young Sasak mothers in Lombok - Bennett, Linda Rae (UI Scholars Hub, 2014)
This article focuses on Indonesian adolescents who are wives and mothers, demonstrating how early marriage and adolescent motherhood are normative among women from poor Sasak communities in Western Lombok. It is based on ethnographic research with 28 young mothers that included focus group discussions, in depth interviews, and observations. Demographic and ethnographic data on the aetiology of early marriage and adolescent motherhood are discussed, and confirm that low educational attainment for girls, lack of employment prospects, poverty, and low levels of economic development are all associated with a higher probability of adolescent marriage and motherhood in Indonesia. The article also reveals how conservative sexual morality and local marriage customs can propel girls into early marriage. It provides a human rights analysis that demonstrates how early marriage and adolescent motherhood intersect with the neglect of girls' rights to education, employment, equality in marriage, health information, family planning, and maternal health.